Prevalence and predictors of metabolically healthy obesity in adolescents: findings from the national “Jeeluna” study in Saudi-Arabia - Lara Nasreddine; Hani Tamim; Aurelie Mailhac; Fadia S. AlBuhairan (BMC Pediatrics, 2018)
Abstract Background Obese children and adolescents may vary with respect to their health profile, an observation that has been highlighted by the characterization of metabolically healthy obesity (MHO). The objectives of this study were to examine the prevalence of MHO amongst obese adolescents in Saudi-Arabia, and investigate the anthropometric, socio-demographic, and lifestyle predictors of MHO in this age group. Methods A national cross-sectional school-based survey (Jeeluna) was conducted in Saudi-Arabia in 2011–2012 (n = 1047 obese adolescents). Anthropometric, blood pressure and biochemical measurements were obtained. A multicomponent questionnaire covering socio-demographic, lifestyle, dietary, psychosocial and physical activity characteristics was administered. Classification of MHO was based on two different definitions. According to the first definition, subjects were categorized as MHO based on the absence of the following traditional cardiometabolic risk (CR) factors: systolic blood pressure (SBP) or diastolic blood pressure (DBP) >90th percentile for age, sex, and height; triglycerides (TG) > 1.25 mmol/L; high density lipoprotein-cholesterol (HDL-C) ≤1.02 mmol/L; glucose ≥5.6 mmol/L. The second definition of MHO was based on absence of any cardiometabolic risk factor, according to the International Diabetes Federation (IDF) criteria. Results The prevalence of MHO ranged between 20.9% (IDF) and 23.8% (CR). Subjects with MHO were younger, less obese, had smaller waist circumference (WC) and were more likely to be females. Based on stepwise logistic regression analyses, and according to the IDF definition, body mass index (BMI) (OR = 0.89, 95% CI: 0.84–0.93) and WC (OR = 0.97, 95% CI: 0.96–0.98) were the only significant independent predictors of MHO. Based on the CR definition, the independent predictors of MHO included female gender (OR = 1.76, 95% CI: 1.29–2.41), BMI (OR = 0.97, 95% CI: 0.94–1.00), and weekly frequency of day napping (OR = 1.06, 95% CI: 1.00–1.12). Analysis by gender showed that vegetables’ intake and sleep indicators were associated with MHO in boys but not in girls. Conclusion The study showed that one out of five obese adolescents is metabolically healthy. It also identified anthropometric factors as predictors of MHO and suggested gender-based differences in the association between diet, sleep and MHO in adolescents. Findings may be used in the development of intervention strategies aimed at improving metabolic heath in obese adolescents.